PENGARUH TINGKAT PERPUTARAN KAS, PIUTANG DAN PERSEDIAAN TERHADAP RENTABILITAS EKONOMI PADA KOPERASI SERBA USAHA SURYA SEKAWAN DI MARTAPURA - Sarmina Sarmina (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
The purpose of this study was to determine and analyze the significant effect of cash, receivables and inventory turnover on economic profitability, either simultaneously or partially at the Surya Sekawan Multipurpose Cooperative in Martapura. This type of research is correlational or causal relationship. The sampling technique used is purpose sampling. The data analysis method used by the author in this study uses multiple linear regression analysis techniques. The results of this study indicate that there is a significant influence on the level of cash turnover, accounts receivable and inventory simultaneously on economic profitability at the Surya Sekawan Multipurpose Cooperative in Martapura. There is a partial significant effect of inventory turnover on economic profitability, while cash turnover and receivables turnover have a partially insignificant effect on economic profitability at the Surya Sekawan Multipurpose Cooperative in Martapura. Inventory turnover has a dominant effect on economic profitability at the Surya Sekawan Multipurpose Cooperative in Martapura.